PMQR genes oqxAB and aac(6′)Ib-cr accelerate the development of fluoroquinolone resistance in Salmonella typhimurium - Wong, Marcus H.; Chan, Edward W.; Liu, Li Z.; Chen, Sheng (Frontiers in Microbiology, 2014)
Emergence of multidrug-resistant S. Typhimurium strains, especially the ACSSuT and nalidixic acid R types, has significantly compromised the effectiveness of current strategies to control Salmonella infections, resulting in increased morbidity and mortality. Clinical S. Typhimurium isolates recovered in Hong Kong during the period of 2005-2011 were increasingly resistant to ciprofloxacin and antibiotics of the ACSSuT group. Our data revealed that oqxAB and aac(6’)Ib-cr were encoded on plasmids of various sizes and the presence of these two elements together with a single gyrA mutation in S. Typhimurium were sufficient to mediate resistance to ciprofloxacin. Acquisition of the oqxAB and aac(6')Ib-cr encoding plasmids by S. Typhimurium caused a 4-fold increase in CIP MIC. Furthermore, the presence of oqxAB and aac(6')Ib-cr in Salmonella dramatically increased the mutation prevention concentration (MPC) of ciprofloxacin which may due to mutational changes in the drug target genes. In conclusion, possession of oqxAB and aac(6’)Ib-cr encoding plasmid facilitate the selection of ciprofloxacin resistant S. Typhimurium, thereby causing a remarkable increase of ciprofloxacin resistance among clinical Salmonella strains in Hong Kong.